RADAR: An In-Building RF-based User Location and Tracking System - Bahl, Victor; Padmanabhan, Venkat (Proceedings of IEEE INFOCOM 2000, 2000)
The proliferation of mobile computing devices and local-area wireless networks has fostered a growing interest in location-aware systems and services. In this paper we present RADAR, a radio-frequency (RF)-based system for locating and tracking users inside buildings. RADAR operates by recording and processing signal strength information at multiple base stations positioned to provide overlapping coverage in the area of interest. It combines empirical measurements with signal propagation modeling to determine user location and thereby enable location-aware services and applications. We present experimental results that demonstrate the ability of RADAR to estimate user location with a high degree of accuracy.
ACM SIGMOBILE Test-of-Time Paper Award, 2016